Multiple‐pass‐enhanced Raman spectroscopy for long‐term monitoring of hydrogen isotopologues. (20th June 2019) - Wen, Chengwei; Huang, Xin; Wang, Weiwei; Shen, Chunlei; Li, Hairong
Abstract: We report a variant of multiple‐pass Raman spectroscopy with enhanced sensitivity for engineering applications. A four‐mirror multiple pass cell is introduced and compared with the conventional two (concave)‐mirror configuration. With this system, gas samples in static cells are measured and monitored. The results show that the noise equivalent detection limit (3σn ) close to 100 ppm for hydrogen isotopologues can be achieved within two seconds with a 1.5‐W red laser. The relative precision is characterized by long‐term measurement, and the results indicate high system stability. The signal‐to‐noise ratio (SNR) in different configurations are investigated, and results show that high (greater than nine) SNR gain is achieved in the configuration of 12 passes. This newly designed Raman system is highly stable and suitable for fast and precise in‐line monitoring of hydrogen isotopologue mixtures, as well as other (hazardous) gas samples. Abstract : A four‐mirror multiple pass cell is introduced with enhanced sensitivity for engineering applications. Noise equivalent detection limit (3σn ) close to 100 ppm for hydrogen isotopologues can be achieved within two seconds with a 1.5‐W red laser. Long‐term measurements of static samples indicate high system stability.